The Representation of Coordinate Relations in Lexical Semantic Memory - Gruenenfelder, Thomas M. (Frontiers in Psychology, 2020)
Experiment 1 examined the size of the typicality effect for true items in a category verification task as a function of the type of false item used. Compared to the case where false items paired unrelated concepts ("carrot-vehicle"), the typicality effect was much larger when false items paired an exemplar with a category coordinate to its proper category ("carrot-fruit"). In contrast, when false items paired coordinate concepts ("carrot-pea") or reversed the ordering of subject and predicate terms ("All vegetables are carrots"), the typicality effect did not change in size. Further, the time to verify true sentences did not increase monotonically with the semantic similarity of the two terms used in false sentences. Experiment 2 showed that the pattern of results for coordinate items reflected semantic processing, not simply task difficulty. Study 1 combined data across multiple experiments, increasing the power of the statistical analysis. The size of the typicality effect when coordinate false items were used was again the same as when false items paired unrelated concepts. The most straightforward explanation of this pattern of results seems to be in terms of a sparse semantic network model of lexical semantic memory, in which labeled links are used to indicate the semantic relation that exists between pairs of words.-3-Coordinate Relations in Semantic Memory